Көші-қон үрдісіндегі оралмандар мəселесінің құқықтық реттелуі - Божқараұлы, А. (ҚарМУ басп, 2010)
Проблема миграции в Казахстане характеризуется особой сложностью, так как в ней переплетены не только правовые вопросы, но и вопросы социологии, демографии, проблемы трудовых ресурсов в экономике. Юридический аспект среди них занимает особое место, так как от надлежащего правового обеспечения, регулирования и организации процессов миграции зависит решение других вопросов, имеющих значение для жизнедеятельности общества. The problem of migration is characterizing with special complexity, as it covers not only legal aspects, but also the problems of sociology, demograthy, ethnogeography, the problems of labor resources in the economics. The legal aspect have the special important place, because the migration is closely connected with the legal security, regulation and organization of migration processes, from which depends other problems of essential value for living conditions of the society.